Engaging Ly‐6A/Sca‐1 triggers lipid raft‐dependent and ‐independent responses in CD4+ T‐cell lines. Issue 4 (28th June 2017) - Lang, Melissa A.; Jenkins, Sultan A.; Balzano, Phillip; Owoyele, Adeyinka; Patel, Akshay; Bamezai, Anil K.
Abstract: Introduction: The lymphocyte antigen 6 (Ly‐6) supergene family encodes proteins of 12–14 kda in molecular mass that are either secreted or anchored to the plasma membrane through a glycosyl‐phosphatidylinisotol (GPI) lipid anchor at the carboxy‐terminus. The lipidated GPI‐anchor allows localization of Ly‐6 proteins to the 10–100 nm cholesterol‐rich nano‐domains on the membrane, also known as lipid rafts. Ly‐6A/Sca‐1, a member of Ly‐6 gene family is known to transduce signals despite the absence of transmembrane and cytoplasmic domains. It is hypothesized that the localization of Ly‐6A/Sca‐1 with in lipid rafts allows this protein to transduce signals to the cell interior. Methods and Results: In this study, we found that cross‐linking mouse Ly‐6A/Sca‐1 protein with a monoclonal antibody results in functionally distinct responses that occur simultaneously. Ly‐6A/Sca‐1 triggered a cell stimulatory response as gauged by cytokine production with a concurrent inhibitory response as indicated by growth inhibition and apoptosis. While production of interleukin 2 (IL‐2) cytokine by CD4 + T cell line in response to cross‐linking Ly‐6A/Sca‐1 was dependent on the integrity of lipid rafts, the observed cell death occurred independently of it. Growth inhibited CD4 + T cells showed up‐regulated expression of the inhibitory cell cycle protein p27 kip but not of p53. In addition, Ly‐6A/Sca‐1 induced translocation of cytochrome C to the cytoplasm along with activated caspase 3 and caspase 9, thereby suggesting an intrinsic apoptotic cell death mechanism. Conclusions: We conclude that opposing responses with differential dependence on the integrity of lipid rafts are triggered by engaging Ly‐6A/Sca‐1 protein on the membrane of transformed CD4 + T cells. Abstract : Ly‐6A/Sca‐1, a member of Ly‐6 gene family is known to transduce signals. Engaging mouse Ly‐6A/Sca‐1 protein trigger cytokine response, growth inhibition, and apoptosis, three functionally distinct responses that occur simultaneously. While IL‐2 cytokine response is dependent on the integrity of lipid rafts, the apoptotic cell death is lipid raft‐independent.